Reading the Mahavamsa: The Literary Aims of a Theravada Buddhist History by Kristin Scheible. - Regan, Julie (Buddhist Studies Review, 2018)
Reading the Mahavamsa: The Literary Aims of a Theravada Buddhist History by Kristin Scheible. Columbia University Press, 2016. 240pp. Hb. $60 (£49.95). ISBN-13: 9780231171380.